Plasma physics: A review and applications with special reference to inertial confinement fusion energy - Jha, Lok N.; Nakarmi, Jeevan J. (Himalayan Journal of Sciences, 2006)
A brief description of plasma, its types and fundamental requirements necessary to study the physics of plasma has been presented through this article. Information given here would be useful to those who have the basic knowledge of physics. Mathematical complications have been avoided to suit the purpose. Varied applications of plasma have been introduced. A little detail has been devoted to one of the major applications of plasma physics known as theoretical thermonuclear fusion studies. Physics of inertial confinement together with the role of self-generated magnetic field in the design of fusion targets have also been described.Himalayan Journal of Sciences 1(1): 21-24, 2003